2020
DOI: 10.1101/2020.08.17.252007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxylipin metabolism is controlled by mitochondrial β-oxidation during bacterial inflammation

Abstract: Oxylipins are potent mediators requiring strict control. How they are removed en masse during infection/inflammation is unknown. Herein, lipopolysaccharide (LPS) dynamically increased their mitochondrial b-oxidation, impacting leukocyte bioactivity. Genetic/pharmacological targeting of CPT1 showed <50 oxylipins were robustly removed by macrophage mitochondria during inflammation in vitro and in vivo. Stable isotope-lipidomics demonstrated secretion-reuptake recycling for 12-HETE and its intermediate metabol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…This results in sufficient amounts present in cell membranes to have an impact on protein association. In this regard, a role for eoxPL in coagulation has been demonstrated in vitro and in vivo , where the calcium dependent association of factors with PS is significantly enhanced by the presence of HETE-PLs in the membrane itself [ 82 , 83 ]. Here, it is proposed that the electronegative -OH group on the eoxPL push the membrane apart, facilitating interactions of calcium ions with the PS headgroup, and enhancing the ability of coagulation factors to associate with the plasma membrane of platelets or eosinophils.…”
Section: The Participation Of Lands Pathway In Development Immunity A...mentioning
confidence: 99%
“…This results in sufficient amounts present in cell membranes to have an impact on protein association. In this regard, a role for eoxPL in coagulation has been demonstrated in vitro and in vivo , where the calcium dependent association of factors with PS is significantly enhanced by the presence of HETE-PLs in the membrane itself [ 82 , 83 ]. Here, it is proposed that the electronegative -OH group on the eoxPL push the membrane apart, facilitating interactions of calcium ions with the PS headgroup, and enhancing the ability of coagulation factors to associate with the plasma membrane of platelets or eosinophils.…”
Section: The Participation Of Lands Pathway In Development Immunity A...mentioning
confidence: 99%
“…A list of oxylipids with retention times (RTs) and MRMs is provided as supplement ( STable 4 ). RTs were determined using pure standards purchased from Cayman Chemical and compared to published data (56, 57). RTs were predicted for oxylipids without pure standard using regressions of known standard RTs (STable 4) .…”
Section: Methodsmentioning
confidence: 99%
“…Oxylipins may act as both pro- and anti-inflammatory molecules [20,21 ▪ ]. Although oxylipins are triggered in response to inflammatory stimuli, a recent study reported that these same stimuli also programme their removal, for example by upregulation of mitochondrial β-oxidation [22 ▪ ]. In general, an increased presence of ω-3 PUFAs in cell membranes leads to an increased generation of less-inflammatory and pro-resolving mediators as a result of LOX and COX action on ω-3 rather than ω-6 PUFAs [20,23,24].…”
Section: Biological Actions Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…DPA is also a substrate for synthesis of SPMs [29]. Recent findings suggest that genetic/pharmacological targeting of carnitine palmitoyl transferase 1, enhances oxylipin removal via mitochondrial β-oxidation independently of oxidative phosphorylation and energy production [22 ▪ ]. Upregulation of many genes is observed in a regulatory metabolic checkpoint for oxylipins during inflammation [22 ▪ ].…”
Section: Biological Actions Of Polyunsaturated Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation